Dietary intakes of dioxins and polychlorobiphenyls (PCBs) and mortality: EPIC cohort study in 9 European countries - Thibault Fiolet; Geneviève Nicolas; Corinne Casagrande; Zsuzsanna Horvath; Pauline Frenoy; Elisabete Weiderpass; Marc J. Gunter; Jonas Manjer; Emily Sonestedt; Domenico Palli; Vittorio Simeon; Rosario Tumino; et al. (International Journal of Hygiene and Environmental Health, 2024)

Diet and lifestyle in relation to small intestinal cancer risk: findings from the European Prospective Investigation into Cancer and Nutrition (EPIC) - Zeynep Ersoy Guller; Rhea N. Harewood; Elisabete Weiderpass; Inge Huybrechts; Mazda Jenab; José María Huerta; Maria-Jose Sánchez; Paula Jakszyn; Pilar Amiano; Eva Ardanaz; Claudia Agnoli; Rosario Tumino; et al. (Cancer Causes & Control, 2023)
Purpose The incidence of small intestinal cancer (SIC) is increasing, however, its aetiology remains unclear due to a lack of data from large-scale prospective cohorts. We examined modifiable risk factors in relation to SIC overall and by histological subtype. Methods We analysed 450,107 participants enrolled in the European Prospective Investigation into Cancer and Nutrition cohort. Cox proportional hazards models were used to estimate univariable and multivariable hazard ratios (HRs) and 95% confidence intervals (CIs). Results During an average of 14.1 years of follow-up, 160 incident SICs (62 carcinoids, 51 adenocarcinomas) were identified. Whilst univariable models revealed a positive association for current versus never smokers and SIC (HR, 95% CI: 1.77, 1.21–2.60), this association attenuated in multivariable models. In energy-adjusted models, there was an inverse association across vegetable intake tertiles for SIC overall (HR T3vsT1 , 95% CI: 0.48, 0.32–0.71, p-trend: < 0.001) and for carcinoids (HR T3vsT1 , 95% CI: 0.44, 0.24–0.82, p-trend: 0.01); however, these attenuated in multivariable models. Total fat was also inversely associated with total SIC and both subtypes but only in the second tertile (SIC univariable HR T2vsT1 , 95% CI: 0.57, 0.38–0.84; SIC multivariable HR T2vsT1 , 95% CI: 0.55, 0.37–0.81). Physical activity, intake of alcohol, red or processed meat, dairy products, or fibre were not associated with SIC. Conclusion These exploratory analyses found limited evidence for a role of modifiable risk factors in SIC aetiology. However, sample size was limited, particularly for histologic subtypes; therefore, larger studies are needed to delineate these associations and robustly identify risk factors for SIC.

Risk of breast cancer in relation to dietary intake of selenium and serum selenium as a marker of dietary intake: a prospective cohort study within The Malmö Diet and Cancer Study - Ylva Bengtsson; Malte Sandsveden; Jonas Manjer (Cancer Causes & Control, 2021)
Purpose Selenium has been suggested to be protective against breast cancer, but the evidence remains inconclusive. Hence, it is important to further examine the potential protective effect. This prospective cohort study investigates pre-diagnostic selenium intake in relation to breast cancer risk. In addition, we analyze serum selenium as a marker of dietary intake. Methods This study includes 17,035 women in the Malmö Diet and Cancer cohort. Dietary assessment and serum samples were collected at baseline (1991–1996). During 344,584 person-years of follow-up, 1,427 incident cases were retrieved. Cox regression analysis examined breast cancer risks adjusted for potential confounding factors. In addition, odds ratios (ORs) were estimated for 1186 cases and an equal number of controls in relation to quartiles (Q) of selenium intake and groups consisting of a combination of intake and serum selenium levels. Results No overall association between selenium intake, or a combination of intake and serum levels, and breast cancer risk was found. The adjusted relative risk for breast cancer in selenium intake Q4 versus Q1 was 0.96 (0.83–1.12) ( P trend = 0.65). Similarly, adjusted the OR for breast cancer in selenium intake for Q4 versus Q1 was 0.97 (0.76–1.23). The kappa value, 0.096 ( p = 0.001), showed poor agreement between serum selenium and selenium intake. Conclusion Our findings suggest that there is no overall association between selenium intake, or a combination of intake and serum levels, and breast cancer risk. Finally, our results showed a poor correlation between estimated selenium intake and serum selenium.

Investigating the risk of breast cancer among women exposed to chemicals: a nested case–control study using improved exposure estimates - Cecilia Videnros; Jenny Selander; Pernilla Wiebert; Maria Albin; Nils Plato; Signe Borgquist; Jonas Manjer; Per Gustavsson (International Archives of Occupational and Environmental Health, 2020)
Purpose The aim of this study was to examine if exposures to chemicals at the workplace were associated with an increased risk of postmenopausal breast cancer, using improved exposure estimates. Methods The design is a case–control study, nested within a cohort of women from the Malmö Diet and Cancer Study. The study comprised 2400 women, 731 cases and 1669 matched controls, born 1923–1950 and living in Malmö, Sweden between 1991 and 1996. An occupational hygienist reclassified the probability for exposure given by a job-exposure matrix, using individual data on work tasks. First-time diagnoses of invasive breast cancer were identified through the Swedish Cancer Registry. Results Women exposed to chemicals in their occupational environment had a statistically significantly increased risk (OR 1.59, 95% CI 1.11–2.29) of breast cancer, and the risk correlated positively with duration of exposure but not with exposure intensity. Women exposed to chlorinated hydrocarbon solvents for more than 10 years had a significant higher risk of breast cancer (OR 3.06, 95% CI 1.18–7.96) as well as women exposed to oil mist for more than 10 years (OR 3.08, 95% CI 1.12–8.49). Conclusions This study gives some support to the hypothesis that exposure to organic solvents as well as oil mist is associated with increased risk of breast cancer.

Vitamin D, PTH, and calcium in relation to survival following prostate cancer - Johan Brändstedt; Martin Almquist; Jonas Manjer; Johan Malm (Cancer Causes & Control, 2016)

Vitamin D, PTH, and calcium and tumor aggressiveness in prostate cancer: a prospective nested case–control study - Johan Brändstedt; Martin Almquist; David Ulmert; Jonas Manjer; Johan Malm (Cancer Causes & Control, 2016)

Prospectively measured thyroid hormones and thyroid peroxidase antibodies in relation to risk of different breast cancer subgroups: a Malmö Diet and Cancer Study - Jasmine Brandt; Signe Borgquist; Jonas Manjer (Cancer Causes & Control, 2015)

Serum levels of vitamin D, parathyroid hormone and calcium in relation to survival following breast cancer - Linnea Huss; Salma Butt; Signe Borgquist; Martin Almquist; Johan Malm; Jonas Manjer (Cancer Causes & Control, 2014)

Pooled cohort study on height and risk of cancer and cancer death - Sara Wirén; Christel Häggström; Hanno Ulmer; Jonas Manjer; Tone Bjørge; Gabriele Nagel; Dorthe Johansen; Göran Hallmans; Anders Engeland; Hans Concin; Håkan Jonsson; Randi Selmer; et al. (Cancer Causes & Control, 2014)

Prospective cohort study of metabolic risk factors and gastric adenocarcinoma risk in the Metabolic Syndrome and Cancer Project (Me-Can) - Björn Lindkvist; Martin Almquist; Tone Bjørge; Tanja Stocks; Wegene Borena; Dorthe Johansen; Göran Hallmans; Anders Engeland; Gabriele Nagel; Håkan Jonsson; Randi Selmer; Guenter Diem; et al. (Cancer Causes & Control, 2013)

Vitamin D, PTH, and calcium and the risk of prostate cancer: a prospective nested case–control study - Johan Brändstedt; Martin Almquist; Jonas Manjer; Johan Malm (Cancer Causes & Control, 2012)

Human immunoglobulin G levels of viruses and associated glioma risk - Sara Sjöström; Ulf Hjalmars; Per Juto; Göran Wadell; Göran Hallmans; Anne Tjönneland; Jytte Halkjaer; Jonas Manjer; Martin Almquist; Beatrice S. Melin (Cancer Causes & Control, 2011)

Consumption of meat and fish and risk of lung cancer: results from the European Prospective Investigation into Cancer and Nutrition - Jakob Linseisen; Sabine Rohrmann; Bas Bueno-de-Mesquita; Frederike L. Büchner; Hendriek C. Boshuizen; Antonio Agudo; Inger Torhild Gram; Christina C. Dahm; Kim Overvad; Rikke Egeberg; Anne Tjønneland; Heiner Boeing; et al. (Cancer Causes & Control, 2011)

Metabolic factors and risk of thyroid cancer in the Metabolic syndrome and Cancer project (Me-Can) - Martin Almquist; Dorthe Johansen; Tone Björge; Hanno Ulmer; Björn Lindkvist; Tanja Stocks; Göran Hallmans; Anders Engeland; Kilian Rapp; Håkan Jonsson; Randi Selmer; Guenter Diem; et al. (Cancer Causes & Control, 2011)

Exposure to environmental tobacco smoke in childhood and incidence of cancer in adulthood in never smokers in the European prospective investigation into cancer and nutrition - Shu-Chun Chuang; Valentina Gallo; Dominique Michaud; Kim Overvad; Anne Tjønneland; Francoise Clavel-Chapelon; Isabelle Romieu; Kurt Straif; Domenico Palli; Valeria Pala; Rosario Tumino; Carlotta Sacerdote; et al. (Cancer Causes & Control, 2011)

Serum triglycerides and cancer risk in the metabolic syndrome and cancer (Me-Can) collaborative study - Wegene Borena; Tanja Stocks; Håkan Jonsson; Susanne Strohmaier; Gabriele Nagel; Tone Bjørge; Jonas Manjer; Göran Hallmans; Randi Selmer; Martin Almquist; Christel Häggström; Anders Engeland; et al. (Cancer Causes & Control, 2011)

Male infertility and prostate cancer risk: a nested case–control study - Yasir Ruhayel; Aleksander Giwercman; David Ulmert; Lars Rylander; Anders Bjartell; Jonas Manjer; Göran Berglund; Yvonne L. Giwercman (Cancer Causes & Control, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Prospective study of physical activity and risk of primary adenocarcinomas of the oesophagus and stomach in the EPIC (European Prospective Investigation into Cancer and nutrition) cohort - José María Huerta; Carmen Navarro; María-Dolores Chirlaque; María-José Tormo; Karen Steindorf; Genevieve Buckland; Fátima Carneiro; Nina Føns Johnsen; Kim Overvad; Jakob Stegger; Anne Tjønneland; Marie-Christine Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Ethanol intake and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition (EPIC) - Sabine Rohrmann; Jakob Linseisen; Alina Vrieling; Paolo Boffetta; Rachael Z. Stolzenberg-Solomon; Albert B. Lowenfels; Majken K. Jensen; Kim Overvad; Anja Olsen; Anne Tjonneland; Marie-Christine Boutron-Ruault; Francoise Clavel-Chapelon; et al. (Cancer Causes & Control, 2009)

Serum calcium and breast cancer risk: results from a prospective cohort study of 7,847 women - Martin Almquist; Jonas Manjer; Lennart Bondeson; Anne-Greth Bondeson (Cancer Causes & Control, 2007)

Fruit and vegetable consumption and lymphoma risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Sabine Rohrmann; Nikolaus Becker; Jakob Linseisen; Alexandra Nieters; Thomas Rüdiger; Ole Raaschou-Nielsen; Anne Tjønneland; Hans E. Johnsen; Kim Overvad; Rudolf Kaaks; Manuela M. Bergmann; Heiner Boeing; et al. (Cancer Causes & Control, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)

Anthropometric factors and risk of endometrial cancer: the European prospective investigation into cancer and nutrition - Christine Friedenreich; Anne Cust; Petra H. Lahmann; Karen Steindorf; Marie-Christine Boutron-Ruault; Françoise Clavel-Chapelon; Sylvie Mesrine; Jakob Linseisen; Sabine Rohrmann; Heiner Boeing; Tobias Pischon; Anne Tjønneland; et al. (Cancer Causes & Control, 2007)

Postmenopausal breast cancer risk in relation to sex steroid hormones, prolactin and SHBG (Sweden) - Jonas Manjer; Robert Johansson; Göran Berglund; Lars Janzon; Rudolf Kaaks; Åsa Ågren; Per Lenner (Cancer Causes & Control, 2003)

Prospective study of IGF-I, IGF-binding proteins, and breast cancer risk, in Northern and Southern Sweden - Rudolf Kaaks; Eva Lundin; Jonas Manjer; Sabina Rinaldi; Carine Biessy; Stefan Söderberg; Per Lenner; Lars Janzon; Elio Riboli; Göran Berglund; Göran Hallmans (Cancer Causes & Control, 2002)